Histological morphology and pathological changes in liver of rats naturally infected with larval stage Cysticercus fasciolaris of Taeniae taeniaeformis: Eman H. Al-Taee1; Omar H. Khalaf1; Fawziaa. S. Kadhim2 and Rajiha A. AL-Naimi1 - Al-Taee, Eman H. (The Iraqi Journal of Veterinary Medicine, 2017)
The aim of this study is to describe the morphology of Cysticercus fasciolaris by using light microscopy, and the pathological changes in the liver of rats naturally infected. A total of 50 liver specimens of local rats (Wister rats) were collected for examination. The gross lesions showed the presence of single or multiple cysts. Microscopic findings revealed the presence of larvae within the cysts which represent the larvae Cysticercus fasciolaris of the adult parasite Taeniae taeniaeformis which inhabited the small intestine of the domestic cats surrounded by fibrous connective tissue infiltrated with inflammatory cells (mononuclear cells and plasma cells). These lesions cause pressure atrophy to the adjacent hepatic parenchyma. In advanced hepatic infection there is a tendency to undergo neoplastic changes (fibroma). Other pathological lesions seen in the liver parenchyma were necrosis, apoptosis with infiltration of chronic inflammatory cells in the portal area, in addition; to formation of early granulomas with congestion of blood vessels which contain neutrophiles in their lumina with extensive area of hemorrhages in liver parenchyma. In conclusion the C. fasciolaris infction induce hepatic neoplasia in rat livers (fibroma) in advance cases of heavy infection, which could be developed to fibrosarcoma in future.